Sosialisasi Dan Pelatihan Sistem Informasi Pengambilan Koordinat Menggunakan Google Map Untuk Pemetaan Kebakaran di Daerah Lahan Basah - Karnanto Hendra Murliawan; Rosalina Kumalawati; Astinana Yuliarti; meldia septiana; syaifuddin syaifuddin; ira puspita dewi; nursalam nursalam; Rizky Nurita anggraeni (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2021)
The Covid-19 pandemic has made all activities carried out online so that technological advances are the focus of development. The purpose of the service is to find out the Coordinate Retrieval Information System Using Google Map for Fire Mapping in Wetlands. The methodology used to use and utilize this application system is the Waterfall Model. Socialization and Training of Android-Based Applications is based on a geographic information system to view and find out the position of a location, for example the location of a settlement in a wetland area that has a high potential for disaster. The stages carried out in this service activity are the preparation stage and the stage of taking coordinates.